KEBIJAKAN FORMULASI TINDAK PIDANA PENCEMARAN NAMA BAIK DALAM BIDANG TEKNOLOGI INFORMASI - Galih Puji Mulyono (Jurnal Cakrawala Hukum, 2017)
The current legal regulation related to the formulation of criminal defamation in information technology is the problem of legal obscurity that causes juridical problem in its implementation. The method used in this research is by normative research method. The approach used to analyze the problem is the approach of the law and the comparative approach. The purpose of this paper is to provide an appropriate view to solve the legal issues raised. Criminal law formulation policies related to criminal defamation in information technology should be conducted through a humanist, cultural and religious value oriented approach integrated into a policy-oriented rational approach. The formulation of criminal defamation should be formulated in detail of subjective and objective elements in criminal defamation. With a formulation policy tailored to the comparative approach of the law that can be used as a contribution to the science of legal obscurity so as not to create multiple interpretations in the meaning of criminal defamation in practice and avoid social conflict.DOI: https://doi.org/10.26905/idjch.v8i2.1669